A COMPARISM BETWEEN A FENTANYLE ALONE OR FENTANYLE AND PROPOFOL IN CONSCIOUS SEDATION IN EYE SURGERY UNDER REGIONAL ANAESTHESIA - Dr. Arena Habeeb Farhan; Dr. Thair Ali Hussein (Scholar Express Journals, 2023)
Regional anesthesia is popular and offers several benefits to the patient and anesthetist. Sedation is part of the general management of a patient receiving a regional block and being awake during the whole surgical procedure.
Keywords: T1DM; thyroid disorder; GADA-Ab